The influence of nurse education and training on communication, emotional intelligence, and empathy - Vicente Javier; María del Carmen; Selene (Revista da Escola de Enfermagem da USP, 2019)
Objective: To determine the influence of nurse education and training on attitudes towards communication, emotional intelligence, and empathy. Method: A cross-sectional study was conducted using three separate instruments to measure attitudes towards communication, empathy, and emotional intelligence, and two questions to determine the academic qualifications of the study participants. The effect of the variables was tested using one-way ANOVA, Pearson correlations, and hierarchical multiple linear regression. Results: The study sample comprised 438 nurses from hospitals in Valencia, Spain. Differences in subscale scores of the instruments according to degree level and specialized training were observed, showing that nurses with only a degree and less specialized training had lower capacity for empathy and emotional intelligence. The strongest correlations were found between the factors of the communication dimensions. Multiple linear regression showed that perspective taking and emotional clarity had the greatest predictive power. Conclusion: Degree level and specialized training were shown to influence the study variables and it is therefore necessary to prioritize education and training programs that promote the development of these skills to ensure improved service quality.